Distal third clavicle fractures: a nationwide trainee-led collaborative review of current practice. (12th December 2022) - Raval, Parag; See, Abbas; Singh, Harvinder P.; ,
Abstract : Aims: Distal third clavicle (DTC) fractures are increasing in incidence. Due to their instability and nonunion risk, they prove difficult to treat. Several different operative options for DTC fixation are reported but current evidence suggests variability in operative fixation. Given the lack of consensus, our objective was to determine the current epidemiological trends in DTC as well as their management within the UK. Methods: A multicentre retrospective cohort collaborative study was conducted. All patients over the age of 18 with an isolated DTC fracture in 2019 were included. Demographic variables were recorded: age; sex; side of injury; mechanism of injury; modified Neer classification grading; operative technique; fracture union; complications; and subsequent procedures. Baseline characteristics were described for demographic variables. Categorical variables were expressed as frequencies and percentages. Results: A total of 859 patients from 18 different NHS trusts (15 trauma units and three major trauma centres) were included. The mean age was 57 years (18 to 99). Overall, 56% of patients (n = 481) were male. The most common mechanisms of injury were simple fall (57%; n = 487) and high-energy fall (29%; n = 248); 87% (n = 748) were treated conservatively and 54% (n = 463) were Neer type I fractures. Overall, 32% of fractures (n = 275) were type II (22% type IIa (n = 192); 10% type IIb (n = 83)). With regards to operative management, 89% of patients (n = 748) who underwent an operation were under the age of 60. The main fixation methods were: hook plate (n = 47); locking plate (n = 34); tightrope (n = 5); and locking plate and tight rope (n = 7). Conclusion: Our study is the largest epidemiological review of DTC fractures in the UK. It is also the first to review the practice of DTC fixation. Most fractures are being treated nonoperatively. However, younger patients, suffering a higher-energy mechanism of injury, are more likely to undergo surgery. Hook plates are the predominantly used fixation method followed by locking plate. The literature is sparse on the best method of fixation for optimal outcomes for these patients. To answer this, a pragmatic RCT to determine optimal fixation method is required. Cite this article: Bone Jt Open 2022;3(12):953–959.